Knowledge, attitudes, and practices of General Practitioners from the Province of Parma (Northern Italy) towards vaccinations in adults ≥ 65 year-old - Vezzosi, Luigi; Riccò, Matteo; Agozzino, Erminia; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Backgrounds and aims: This study aims to characterize attitudes and knowledge towards immunization practice of people aged >65 years for seasonal influenza (SIV), pneumococcus (PNV), and Herpes zoster (ZV) in a sample of Italian general practitioners (GPs). Materials and Methods: During 10/2018, a structured questionnaire was emailed to 274 GPs operating in the Province of Parma, Italy. Association between willingness to perform aforementioned vaccines and individual factors was assessed through a multivariate regression analysis by calculating multivariate Odds Ratio (mOR). Results: A total of 73 GPs (26.6% of original sample) completed the questionnaire. Knowledge gaps were identified on the targeted vaccination rates for PNV and ZV (31.6% and 21.9% of correct answers), on the formulation of VZ (41.1%), and on the simultaneous immunization SIV/ZV (12.3%). The majority of respondents had high/very high trust on safety and efficacy of assessed vaccines. In multivariate analysis, recommending PNV was associated with having previously received SIV (mOR 5.44, 95%CI 1.08-27.31). In turn, ZV was negatively associated with a self-assessed knowledge gap (mOR 0.07, 95%CI 0.01-0.63). Discussion: Despite a generally favorable attitude towards vaccines, GPs exhibited knowledge gaps deserving appropriate intervention. However, lack of association between knowledge status and willingness to vaccinate enlighten the complex interplay between attitudes and personal behaviors.